Aislamiento social y trastornos emocionales de las personas adultas mayores de la parroquia Yangana de Loja - Ochoa Ríos, Patricio (2013)
The SOCIAL ISOLATION AND EMOTIONAL DISORDERS OF OLDER PEOPLE OF THE PARISH OF YANGANA OF LOJA, is a study of Descriptive type cross -interpretative and, as a result relevant are: That the parish live 1529 people of which 185 are Senior Citizens, the sample is made up of 85 individuals living in the parish center, which during the course of the investigation did not wish to participate 15 people staying the same for Seniors 70 of which 40 are women and 30 men. All Seniors and caregivers both agree that an insufficient number and quality of sports, recreational and cultural developed. 70% of people say do some social activity and it is with family and neighbors while the remaining 30% never do. The 60 % of people is done once a month, 28.58 % and 8.58% never when they have time. 77% have good communication and relationships. What's remarkable is obtained that 36.6 % feel a dependent, and 60% believe it is due to old age situation and 7 % are not satisfied with the terms of his family. Being able to get to determine that there is a relationship between social isolation and the onset of emotional disorders in the elderly of the parish Yangana. It raised the design and offer Yangana Parish Board a proposed comprehensive development for older people in Yangana, the same consisting of a series of activities designed to link the older person to the community with the support of family friends and institutions interact to it.